Holes - SACHAR, LOUIS; LOUIS SACHAR (USA Yearling, 2015)
Stanley Yelnats IV, a boy wrongly convicted of theft and sent to a Texas juvenile detention camp, Camp Green Lake.
Keywords: The core narrative focuses on themes of fate, friendship, and overcoming adversity; individuals can overcome bad fate and adversity through friendship, resilience, and personal choices